The Influence Of Leadership Style, Work Motivation And Quality Of Work Life On Job Satisfaction Of Dompu Regency General Hospital Employees - Arif Hidayatullah; I Nyoman Nugraha; Maman Rumanta; Syati Irawati; Sri Astuti Handayani (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to (1) provide empirical evidence that leadership style, work motivation and quality of work life partially affect employee job satisfaction at the Dompu Regency General Hospital, and (2) provide empirical evidence that leadership style, work motivation and quality of work life simultaneously affect employee job satisfaction at the Dompu Regency General Hospital. The population of this study was 248 people with a sample of 71 respondents. The data of this study were analyzed using descriptive statistics and multiple linear regression with the help of SPSS 16. The results of this study show that leadership style, work motivation and quality of work life have a positive and significant effect partially or simultaneously on employees’ job satisfaction at the Dompu Regency General Hospital. A good leadership style and in accordance with the right situation and successful leadership depends on the right behavior, skills and actions, so as to provide work motivation to employees by paying attention to physiological needs, security, the need for a sense of belonging (social) and the need for self-esteem and the need to self-actualize.